Metabolic assessment in children with neuromuscular disorders shows risk of liver enlargement, steatosis and fibrosis. (12th January 2023) - Naume, Marie Mostue; Jørgensen, Marianne Hørby; Høi‐Hansen, Christina Engel; Born, Alfred Peter; Vissing, John; Borgwardt, Lise; Stærk, Dorte Marianne Rohde; Ørngreen, Mette Cathrine
Abstract: Aim: The aim of this study was to conduct a metabolic and nutritional assessment of children with neuromuscular disorders, including the investigation of the liver and bone mineral density. Methods: In this observational study, we included 44 children with neuromuscular disorders. The nutritional status, bone health and liver were assessed by ultrasound, transient elastography, dual X‐ray absorptiometry scan, blood samples, anthropometric measurements and 3‐day diet registration. Results: Liver involvement was found in 31.0%: liver enlargement in 7.1%, steatosis in 4.8%, fibrosis in 14.3% and liver enlargement together with steatosis or fibrosis was found in 4.8%. These changes were found in 9/23 patients with Duchenne muscular dystrophy, 4/9 patients with spinal muscular atrophy type II and 0/12 patients with other neuromuscular diagnoses. Low bone mineral density was found in 44.0% of the patients, though the majority used daily vitamin D and calcium supplements. Vitamin D insufficiency or deficiency was found in 22.6%. Conclusion: The metabolic assessment in children with neuromuscular disorders shows an increased risk of liver enlargement, steatosis and fibrosis. Possible causes are obesity, decreased mobility, low skeletal muscle mass and for a subgroup the use of glucocorticoids. The findings suggest that monitoring liver function should be part of the nutritional assessment in patients with neuromuscular disorders.